Genetic structuring among colonies of a pantropical seabird: Implication for subspecies validation and conservation. Issue 21 (29th September 2020) - Humeau, Laurence; Le Corre, Matthieu; Reynolds, S. James; Wearn, Colin; Hennicke, Janos C.; Russell, James C.; Gomard, Yann; Magalon, Hélène; Pinet, Patrick; Gélin, Pauline; Couzi, François‐Xavier; Bemanaja, Etienne; et al.
Abstract: Investigations of the genetic structure of populations over the entire range of a species yield valuable information about connectivity among populations. Seabirds are an intriguing taxon in this regard because they move extensively when not breeding, facilitating intermixing of populations, but breed consistently on the same isolated islands, restricting gene flow among populations. The degree of genetic structuring of populations varies extensively among seabird species but they have been understudied in their tropical ranges. Here, we address this across a broad spatial scale by using microsatellite and mitochondrial data to explore the population connectivity of 13 breeding populations representing the six subspecies of the white‐tailed tropicbird ( Phaethon lepturus ) in the Atlantic, Indian, and Pacific Oceans. Our primary aim was to identify appropriate conservation units for this little known species. Three morphometric characters were also examined in the subspecies. We found a clear pattern of population structuring with four genetic groups. The most ancient and the most isolated group was in the northwestern Atlantic Ocean. The South Atlantic populations and South Mozambique Channel population on Europa were genetically isolated and may have had a common ancestor. Birds from the Indo‐Pacific region showed unclear and weak genetic differentiation. This structuring was most well defined from nuclear and mtDNA markers but was less well resolved by morphological data. The validity of classifying white‐tailed tropicbirds into six distinct subspecies is discussed in light of our new findings. From a conservation standpoint our results highlight that the three most threatened conservation units for this species are the two subspecies of the tropical North and South Atlantic Oceans and that of Europa Island in the Indian Ocean. Abstract : Morphology and population genetic structure of the white‐tailed tropicbird ( Phaethon lepturus ) over its entire range were analyzed in order to investigate population connectivity and relatedness. Our results are an example of how thorough genetic analyses can reveal critical information about subspecies delimitation and conservation priorities.